2002
DOI: 10.1136/aim.20.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acupuncture on Knee Function in Advanced Osteoarthritis of the Knee: A Prospective, Non-Randomised Controlled Study

Abstract: We report a prospective controlled trial, comparing acupuncture with no treatment, in patients with advanced osteoarthritis of the knee awaiting total knee replacement. Knee function was assessed at the beginning of study and at the end of two months, using four parameters: HSS score, time to walk 50 metres, time to climb 20 steps, and degree of pain. Acupuncture was given at four local points around the knee and at one distal point. The acupuncture group improved in all parameters, whereas the control group d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
2

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 7 publications
2
12
0
2
Order By: Relevance
“…When individual CAM modalities were analyzed, significant reduction in pain was still realized for acupuncture, chiropractic, and naturopathy. Prior evaluations of pain in acupuncture and chiropractic using analogue scales have been carried out by a number of researchers with varied results (Bulow et al, 1992;David et al, 1999;Leibing et al, 2002;McMorland and Suter, 2000;Molsberger et al, 2002;Nyiendo et al, 2000Nyiendo et al, , 2001Pellow and Brantingham, 2001, Tillu et al, 2002Wood et al, 2001). Molsberger et al (2002) demonstrated a significant reduction in back pain using acupuncture when comparing three groups of patients; real acupuncture and orthopedic care, sham acupuncture and orthopedic care, and orthopedic care alone.…”
Section: Discussionmentioning
confidence: 96%
“…When individual CAM modalities were analyzed, significant reduction in pain was still realized for acupuncture, chiropractic, and naturopathy. Prior evaluations of pain in acupuncture and chiropractic using analogue scales have been carried out by a number of researchers with varied results (Bulow et al, 1992;David et al, 1999;Leibing et al, 2002;McMorland and Suter, 2000;Molsberger et al, 2002;Nyiendo et al, 2000Nyiendo et al, , 2001Pellow and Brantingham, 2001, Tillu et al, 2002Wood et al, 2001). Molsberger et al (2002) demonstrated a significant reduction in back pain using acupuncture when comparing three groups of patients; real acupuncture and orthopedic care, sham acupuncture and orthopedic care, and orthopedic care alone.…”
Section: Discussionmentioning
confidence: 96%
“…There was also insufficient evidence for the authors to determine whether the efficacy of acupuncture was similar to that of other treatments. Since the completion of the systematic review a non-rondomized trial has been published [13], in which the acupuncture group showed improved pain and function in patients with osteoarthritis of the knee.…”
Section: State Of Research On Acupuncture For Osteoarthritis Of the Kneementioning
confidence: 99%
“…[3][4][5][6][7] Many patients suffering from OA of the knee, who have not been helped by one or more Western therapy regimes, find relief from alternative medical approaches, including acupuncture. [8][9][10][11][12][13][14][15][16][17][18][19] A survey in 1996 showed that more than 50% of all cases treated by acupuncturists in the UK had OA. 20 It has been suggested that acupuncture, with its good safety record, [21][22][23] can be used to manage OA in patients for whom conventional Western treatments are inadequate or contraindicated.…”
Section: Introductionmentioning
confidence: 99%